2022
DOI: 10.31083/j.rcm2307238
|View full text |Cite
|
Sign up to set email alerts
|

Sacubitril/valsartan in Heart Failure and Beyond—From Molecular Mechanisms to Clinical Relevance

Abstract: As the ultimate pathophysiological event, heart failure (HF) may arise from various cardiovascular (CV) conditions, including sustained pressure/volume overload of the left ventricle, myocardial infarction or ischemia, and cardiomyopathies. Sacubitril/valsartan (S/V; formerly termed as LCZ696), a first-in-class angiotensin receptor/neprilysin inhibitor, brought a significant shift in the management of HF with reduced ejection fraction by modulating both renin-angiotensin-aldosterone system (angiotensin II type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 170 publications
(270 reference statements)
0
4
0
Order By: Relevance
“…A clear and early benefit of S/V was to reduce hospital readmissions of HF patients due to any causes. 7 McMurray et al and Desai et al pointed out all-cause readmission at 3 months or 1 year. 9 Unfortunately, there remained poor understanding of novel-dose S/V.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A clear and early benefit of S/V was to reduce hospital readmissions of HF patients due to any causes. 7 McMurray et al and Desai et al pointed out all-cause readmission at 3 months or 1 year. 9 Unfortunately, there remained poor understanding of novel-dose S/V.…”
Section: Introductionmentioning
confidence: 99%
“…A clear and early benefit of S/V was to reduce hospital readmissions of HF patients due to any causes. 7 McMurray et al and Desai et al pointed out that S/V was superior to enalapril in improving HF patient outcomes. 3,8 Lately, Carnicelli et al reported that patients with higher adherence to S/V showed a significant reduction in all-cause readmission at 3 months or 1 year.…”
Section: Introductionmentioning
confidence: 99%
“…A clear and early benefit of S/V was to reduce hospital readmissions of HF patients due to any causes 11 . McMurray et al and Desai et al pointed out that S/V was superior to enalapril in improving HF patient outcomes 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Heart failure (HF) is a potential outcome of end stage of heart disease. It impairs the cardiac circulation due to a systolic and/or diastolic function damage of the heart [ 1 , 2 ]. HF occurs mainly due to remodeling of heart muscle cells [ 3 ].…”
Section: Introductionmentioning
confidence: 99%